2014
DOI: 10.1117/1.nph.1.1.011014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the BAC Id3-enhanced green fluorescent protein transgenic mouse line forin vivoimaging of astrocytes

Abstract: Astrocytes are highly ramified glial cells with critical roles in brain physiology and pathology. Recently, breakthroughs in imaging technology have expanded our understanding of astrocyte function in vivo. The in vivo study of astrocytic dynamics, however, is limited by the tools available to label astrocytes and their processes. Here, we characterize the bacterial artificial chromosome transgenic Id3-EGFP knock-in mouse to establish its usefulness for in vivo imaging of astrocyte processes. Using fixed brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…By contrast, Id3 is highly expressed in neural tissues (Figure S3c,h). Double labeling experiments confirmed that all Id3 + cells outside the germinal zone are ALDH1L1+ astrocytes (Figure S3i), as reported by previous studies (Batiuk et al, 2020; Lamantia et al, 2014; Li et al, 2021). Collectively, these data argued against the expression of Id1 and Id3 in oligodendroglial cells during development.…”
Section: Discussionsupporting
confidence: 88%
“…By contrast, Id3 is highly expressed in neural tissues (Figure S3c,h). Double labeling experiments confirmed that all Id3 + cells outside the germinal zone are ALDH1L1+ astrocytes (Figure S3i), as reported by previous studies (Batiuk et al, 2020; Lamantia et al, 2014; Li et al, 2021). Collectively, these data argued against the expression of Id1 and Id3 in oligodendroglial cells during development.…”
Section: Discussionsupporting
confidence: 88%
“…Several of these glial (progenitor) populations can be identified by expression of the transcription factors Id3, Sox9, Olig2, and NFIA. Previous studies in rodents showed that Id3 is only expressed in developing astrocytes (Lamantia, Tremblay, & Majewska, 2014;Molofsky et al, 2013). Sox9 is initially (E8.5-E18.5) expressed in all glial (precursor) cells, and is subsequently downregulated in myelinating oligodendrocytes (Stolt et al, 2003) and becomes astrocyte-specific (Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These important observations confirmed Achúcarro and Río-Hortega's hypothesis that microglia are extremely dynamic (Achúcarro, 1909 ; Río-Hortega, 1919b ). The degree of their structural plasticity surpassed all expectations: microglial processes were found to survey their surrounding environment on a time scale of minutes, in contrast to neurons and other types of neuroglial cells which show no comparable structural remodeling in vivo (Majewska and Sur, 2003 ; Eom et al, 2011 ; Hughes et al, 2013 ; Lamantia et al, 2014 ). With these observations, microglia have emerged as the most dynamic cell type of the mature CNS.…”
Section: The Renaissance Of Functional Neuroanatomymentioning
confidence: 92%